HUBUNGAN PERILAKU ASERTIF DENGAN PRESTASI BELAJAR SISWA KELAS V SEKOLAH DASAR - Kautsar Fathurrahman, - (2021)
This study aims to describe the level of assertive behavior and learning achievement and the level of relationship between students' assertive behavior and learning achievement of grade V elementary school students in Bandung. This study used a quantitative approach with correlational or relationship research methods. Based on the data that has been obtained in the study, it is concluded that the assertive behavior of grade V elementary school students at SDN TG5 and SDN TG3 in Bandung is predominantly in the high category, a small portion is very high, for the moderate category it is less than the low category, and the number of very low category is tiny. The level of learning achievement of students in class V SDN TG5 and TG3 in the city of Bandung is predominantly in the high category, only slightly different from the low category, the moderate category is more from the very low category, and the very high category is very little in number. The significance value is 0.243> 0.05 and the degree of closeness of the relationship is 0.145 away from 1 with a determination coefficient of 0.21. It is concluded that there is no significant positive relationship between assertive behavior and student achievement of grade V Elementary School however, there is a degree of association with the low / weak category. Assertive behavior partially affects learning achievement only a little, while most of it is influenced by other variables outside the regression equation or variables not examined in this study.